Digital next‐generation sequencing of cell‐free DNA for pancreatic cancer - Shinichi Takano; Mitsuharu Fukasawa; Hiroko Shindo; Ei Takahashi; Yoshimitsu Fukasawa; Satoshi Kawakami; Hiroshi Hayakawa; Natsuhiko Kuratomi; Makoto Kadokura; Shinya Maekawa; Nobuyuki Enomoto (JGH Open, 2021)
Abstract Background and Aim The clinical applicability of digital next‐generation sequencing (dNGS), which eliminates polymerase chain reaction (PCR) and sequencing error‐derived noise by using molecular barcodes (MBs), has not been fully evaluated. We evaluated the utility of dNGS of cell‐free DNA (cfDNA) in liquid biopsies obtained from patients with pancreatic cancer. Methods Fifty‐eight patients with pancreatic cancer undergoing endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) were included. Samples were subjected to sequencing of 50 cancer‐related genes using next‐generation sequencing (NGS). The results were used as reference gene alterations. NGS of cfDNA from plasma was performed for patients with a mutant allele frequency (MAF) >1% and an absolute mutant number > 10 copies/plasma mL in KRAS or GNAS by digital PCR. Sequence readings with and without MBs were compared with reference to EUS‐FNA‐derived gene alterations. Results The concordance rate between dNGS of cfDNA and EUS‐FNA‐derived gene alterations was higher with than without MBs (p = 0.039), and MAF cut‐off values in dNGS could be decreased to 0.2%. dNGS using MBs eliminated PCR and sequencing error by 74% and 68% for TP53 and all genes, respectively. Overall, dNGS detected mutations in KRAS (45%) and TP53 (26%) and copy number alterations in CCND2, CCND3, CDK4, FGFR1, and MYC, which are targets of molecular‐targeted drugs. Conclusions dNGS of cfDNA using MBs is useful for accurate detection of gene alterations even with low levels of MAFs. These results may be used to inform the development of diagnostics and therapeutics that can improve the prognosis of pancreatic cancer.